Comparison of the effectiveness of education methods between quartet card games and lectures on students' oral health knowledge - Ardlina, Nira; Poetri, Adisty Restu; Nugrahani, Muqsitha Fitri; Paramartha, Rizki Widya (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background: This study aims to determine the differences in the effectiveness of education methods between the quartet card game method and the lectures method on the level of students' oral health knowledgeMethod: This study uses a cross-sectional study method. The subjects were 30 students of SD Islam Terpadu Asshodiqiyah Semarang by aged 11-12 years old. The subjects receive dental and oral health education. One group received education using the quartet card game method and the other group received education using the lectures method. The level of students' oral health knowledge was measured using a questionnaire (pre test and post test).Result: The Wilcoxon test results showed a significant difference between the pre-test and post-test scores of the quartet game method (p=0.036). There was a significant difference between the pre-test and post-test scores of the lecture method (p=0.002). The Mann-Whitney test results showed no significant difference between the post-test scores of the quartet card game method and the test scores of the lecture method (p=0.254).Conclusion: Quartet card games can be used as an alternative learning method that can increase student involvement in learning, resulting in good knowledge retention